Efficient Production of Yeast Cu-Zn Superoxide Dismutase in the Periplasm of Escherichia coli by Co-expression of Skp Molecular Chaperone (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Co-expression is a simultaneous expression of two or more proteins. Molecular chaperons are proteins that naturally produced in the cell and have an important role to restrain aggregation of non-native protein production. Co-expression of target protein along with molecular chaperone is an efficient way to overcome the problems faced during expression of recombinant proteins. The present study aims at co-expressing protein that is highly useful in cosmetics, Superoxide dismutase in periplasm of E. coli with molecular chaperone Skp. To maintain expression levels between Superoxide dismutase (SOD) and Skp, both proteins were placed under the control of different promoter and terminator systems in a single vector. Effect of co-expression of Skp chaperone on cell growth, SOD protein yield and SOD enzyme activity were evaluated. Skp co-expression found effective in all three aspects. The yield of Cu-Zn Superoxide dismutase increased from 30.92mg/L to 52.01mg/L when Skp chaperon is co-expressed. No detectable free SOD subunits were observed on western blot, which established method of Skp co-expression could be applied to tackle problem of unprocessed free protein subunits while expressing recombinant protein in E. coli periplasm.